2018
DOI: 10.1002/pi.5678
|View full text |Cite
|
Sign up to set email alerts
|

[60]Fullerene‐quinoxaline, benzothiadiazole and benzoselenadiazole based dyads for thermally stable polymer solar cells: anchoring of substituent on fullerene with a poly(3‐hexylthiophene) polymer chain

Abstract: [6,6]‐Phenyl‐C61‐butyric acid methyl ester (PC61BM and PC71BM) is an archetypal electron acceptor in organic photovoltaic devices. However, it nucleates and grows to form aggregates or crystallites on a length scale of tens of nanometres to micrometres under thermal aging, which often results in a significant decrease in device efficiency and stability. To overcome this thermally induced performance degradation, many methods have been reported to date such as the introduction of hydrogen, halogen bonding, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…linked three types of bulkier qulnoxaline (TQT), benzothiadiazole (TTBT), and benzoselenadiazole (TBST) to the fullerene acceptor and designed three modified novel fullerene acceptors TQT‐C 60 , TBTT‐C 60 , and TBST‐C 60 (as shown in Figure ), respectively. [ 196 ] When paired with donor P3HT, they found that all three types of modified fullerene based devices showed excellent thermal stability which all maintained over 90% of its initial PCE after being heated at 130 °C for 5 h. They proved that those added bulkier groups could act as an anchoring group to suppress the aggregation of fullerene acceptors in the active layer during the aging. Recently, Brabec et al.…”
Section: Progress In Enhancing Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…linked three types of bulkier qulnoxaline (TQT), benzothiadiazole (TTBT), and benzoselenadiazole (TBST) to the fullerene acceptor and designed three modified novel fullerene acceptors TQT‐C 60 , TBTT‐C 60 , and TBST‐C 60 (as shown in Figure ), respectively. [ 196 ] When paired with donor P3HT, they found that all three types of modified fullerene based devices showed excellent thermal stability which all maintained over 90% of its initial PCE after being heated at 130 °C for 5 h. They proved that those added bulkier groups could act as an anchoring group to suppress the aggregation of fullerene acceptors in the active layer during the aging. Recently, Brabec et al.…”
Section: Progress In Enhancing Stabilitymentioning
confidence: 99%
“…Figure 20. Chemical structure diagrams of modified novel fullerene acceptors TQT-C 60 , TBTT-C 60 , and TBST-C 60 .Reproduced with permission [196]. Copyright 2018, John Wiley and Sons.…”
mentioning
confidence: 99%
“…The researchers found that TQT-C 60 demonstrated enhanced morphological stability and thermal resistance compared to the phenyl-C61butyric acid methyl ester (PCBM) acceptor when used in bulk heterojunction polymer solar cell devices with poly(3-hexylthiophene) (P3HT) as the donor material. This improvement was attributed to the anchoring effect of the bulkier groups present in TQT-C 60 , which hindered the movement and aggregation of fullerene molecules within the polymer matrix [25]. The introduction of functional groups provided a strategic means to tailor the molecular structure, resulting in improved photovoltaic properties and overall PCEs (12.12-13.3%) [29].…”
Section: Quinoxalines As Nfasmentioning
confidence: 99%